(5,86:1,78) +(14,98:1,88)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(1,78^{2x-2}-1,78^x\right):1,78^x=0\)
\(\Rightarrow1,78^{2x-2-x}-1,78^{x-x}=0\)
\(\Rightarrow1,78^{x-2}=1\Rightarrow x-2=0\Rightarrow x=2\)
<=> 1,782x-2 - 1,78x = 0
<=> 1,782x-2 = 1,78x
<=> x không tồn tại.
34,98 - (12,5 + 14,98) = 34,98 - 12,5 - 14,98 = (34,98 - 14,98) - 12,5 = 20 - 12,5 = 7,5
87,45 - 36,09 - 34,91 = 87,45 - (36,09 + 34,91) = 87,45 - 71 = 16,45
a)(x - 1) x + 2 = (x - 1)x + 4
=> (x - 1) x + 4 - (x - 1)x + 2 = 0
=> (x - 1)x + 2 . [(x - 1)2 - 1] = 0
=> \(\orbr{\begin{cases}\left(x-1\right)^{x+2}=0\\\left(x-1\right)^2-1=0\end{cases}\Rightarrow\orbr{\begin{cases}\left(x-1\right)^{x+2}=0^{x+2}\\\left(x-1\right)^2=1^2\end{cases}\Rightarrow}\orbr{\begin{cases}x-1=0\\x-1=\pm1\end{cases}}}\)
Nếu x - 1 = 0
=> x = 1
Nếu x - 1 = - 1
=> x = 0
Nếu x - 1 = 1
=> x = 2
Vậy \(x\in\left\{0;1;2\right\}\)
b) \(\left(1,78^{2x-2}-1,78^x\right):1,78^x=0\)
\(\Rightarrow1,78^{2x-2}:1,78^x-1,78^x:1,78^x=0\)
\(\Rightarrow1,78^{x-2}-1=0\)
\(\Rightarrow1,78^{x-2}=1\)
\(\Rightarrow1,78^{x-2}=1,78^0\)
\(\Rightarrow x-2=0\)
\(\Rightarrow x=2\)
Vậy x = 2